Mineração de genes em regiões genômicas bovinas associadas à resistência ao carrapato Rhipicephalus (Boophilus) microplus - Catoia, Vitor (Universidade Federal de São Carlos, 2014)
The Brazilian cattle industry is presented as highlighted on the world stage and the significant participation of this productive sector in the economy means that there is concern with production losses, among which stands out those caused by infestation of Rhipicephalus (Boophilus) microplus, main ectoparasite vector cattle and various diseases. The genetic variability for resistance to the cattle tick shows that this trait can be genetically improved. For the execution of this work, it was used a study of genome wide association (GWAS) for resistance to Rhipicephalus (Boophilus) microplus, performed by Dr. Fernando Flores Cardoso, with 260 Hereford and 500 Braford animals. The monitoring of the infestation was accomplished by counting tick females larger than 4.5 mm from one of the animal's body side, and the degree of infestation was evaluated for each animal by averaging at least two consecutive counts, with intervals of approximately thirty days, in the months of highest incidence of the parasite. The animals were genotyped using a 50K SNP chip, and it was found a total of 37,346 SNPs that passed in quality test. Among these markers, 178 showed significant effects and allowed the mining of 175 genes in these regions, at an interval of 200 Kb (100 Kb for each side of each marker). Most of these polymorphisms associated with the trait is located in regions without defined functions (intronic and intergenic), and only one of them is located in the splicing region. The most significant regions of the GWAS were identified on chromosomes 7, 21 and 23, which were found 72 genes in linkage disequilibrium with the molecular markers. Therefore, a functional annotation of the genes on these 3 chromosomes was performed, allowing the choice of 11 candidate genes for the study of various metabolic pathways in which they are inserted. Among these pathways, the most important are those related to immune responses, secretion and intracellular transport, calcium influx and epidermal growth and differentiation.
Keywords: Genética; Animais - melhoramento genético; Infestação; Genome Wide Association Study (GWAS); Rhipicephalus (Boophilus) microplus; Candidate genes for tick resistance; Metabolic pathways; CIENCIAS BIOLOGICAS::GENETICA